Sural nerve biopsy and functional studies support the pathogenic role of a novel MPZ mutation. Issue 3 (11th November 2014) - Prada, Valeria; Capponi, Simona; Ursino, Giulia; Alberti, Antonia; Callegari, Ilaria; Passalacqua, Mario; Marotta, Roberto; Mandich, Paola; Bellone, Emilia; Schenone, Angelo; Grandis, Marina
<x xml:space="preserve">Abstract</x> Our patient is a 65‐year‐old woman presenting with bilateral pes cavus, pronounced distal muscle wasting, weakness and areflexia. Electrophysiological findings included diffuse unrecordable motor and sensory responses. While the CMT phenotype was evident, the lack of family history and the severe, but unspecific electrophysiological impairment, was a challenge for genetic diagnosis. A sural nerve biopsy was performed, showing a severe loss of myelinated fibers with residual axons surrounded by myelin outfoldings. Whereas myelin outfoldings are a pathological hallmark of autosomal recessive CMT4B1 and CMT4B2, due to mutations in myotubularin‐related 2 (MTMR2) and 13 (MTMR13) genes respectively, they may also occur in nerve biopsies from CMT1B patients. By direct sequencing, a novel heterozygous transversion c.410G>T in MPZ gene was demonstrated, producing an amino acid change from glycine to valine in position 108 (p.G108V). In HeLa cells the fusion P0G108V‐EGFP was normally trafficked to the cell membrane, but with decreased P0 adhesion function, compared with wild‐type P0, thus supporting a pathogenic role of the new variant. In conclusion this case highlights the relevance, in selected cases, of sural nerve biopsy to orient the genetic/molecular tests, while in vitro analyses may strengthen the pathogenic role of novel mutations.